Rewriting the phase diagram of a diamagnetic liquid crystal by a magnetic field - Hajjaj, Fatin (Nat Commun, 2018)
Magnetic fields have been considered to only interact with organic materials non-destructively, leaving their fundamental structures unaffected, even when a strong magnetic field generated from a superconducting magnet is applied. Here we report an unprecedented observation that a liquid-crystalline mesophase of a diamagnetic molecular assembly with an orthorhombic or a cubic structure is formed selectively in the absence or presence of a strong magnetic field. The constituent molecule is a triphenylene derivative carrying six imidazolium bromide-terminated alkyl side chains and exhibits a cubic, orthorhombic, or hexagonal columnar mesophase when complexed with an appropriate amount of lanthanum(III) bromide. Thermal processing of the La(3+)-containing liquid-crystalline assembly in the presence of a 10-tesla magnetic field resulted in a phase diagram, in which the orthorhombic phase is completely replaced with the cubic phase. The discovery of this magneto-induced phase-selection offers an insight into the interactions between magnetic fields and organic material.